En el centenario de su nacimiento (1902-2002) : Karl Popper y la epistemología contemporánea (2003)
ABSTRACT: What means the thought of Popper at the present time? What importance has east philosopher for us to eight years of its death (London, 1994) and to one hundred years of its birth (Vienna, 1902)? What I contribute made Popper to the knowledge, the methodology, the Scientific Philosophy, and in special, what I contribute can be in its theory and epistemología for Social Sciences?